Kriteria Perencanaan Jalan dalam Penyusunan Detail Engineering Design (DED) Studi Kasus Desa Pingaran Ulu-Kahelaan - Dewi, Norminawati (Jurnal Sains dan Teknologi (JSIT), 2024)
Banjar Regency is a district in South Kalimantan. The capital of Banjar Regency is in the city of Martapura. Banjar Regency is one of the regencies in South Kalimantan Province with an area of 4,668.50 KM2. Divided into 19 sub-districts with 277 villages, 13 sub-districts and based on the 2010 census results, the population is 506,839 people. To support community movement and increase economic growth, the Banjar Regency government pays close attention to road performance. In road planning, the emphasis is always on planning the physical form so that it can fulfill the basic function of the road, namely providing optimum service to traffic flow. So in this planning efforts are made to create a good relationship between space and time so that it can produce optimal efficiency, safety and comfort. The space, shape and size of a road can be said to be good if it can provide a feeling of safety and comfort to road users. From the results of planning the road criteria for the PINGARAN ULU - KAHELAAN DED which has been carried out in accordance with existing conditions and needs, the following conclusion can be made: The Pingaran Ulu - Kahelaan Section has a length of 50.11 km, with handling adjusting for damage in the field, which is 19 km long. ,00 km. The existing condition of the road section has a slope of 4% - 8%, and the surrounding area is residential and plantations. Handling Plan: Road Reconstruction Work (Sta. 34 + 000 – Sta. 53 + 000).